THE UNIQUENESS OF TEACHING THE SUBJECT "STAGE SPEECH" IN THE DIRECTION OF PUPPET THEATER ACTING - Yusupova Venera Ismetovna (Bright Mind Publishing, 2025)
This article reveals the features of education speech voice actors puppet theater. Makes recommendations for recognizing professional aptitude voice data entrants branch "of the puppet theater actor." Also talks about the different systems and methods for their dolls "sound."
Keywords: Psychotechnics of the puppeteer actor, doll